'A lesson in football wisdom'? Coverage of the unofficial women's World Cup of 1971 in the Mexican press. Issue 2 (3rd April 2019) - Brewster, Claire; Brewster, Keith
ABSTRACT: When Mexico hosted the 1971 Women's World Cup, it raised considerable challenges for local journalists. The domestic game had never received significant press attention, but mounting public interest in such a prestigious tournament demanded a response from national and sporting newspapers. In this chapter, we analyse the extent to which the masculine hegemonic environment of the newsroom dictated the perspective, language, and imagery deployed by journalists in their reports. While underlying sexism and cynicism characterised more traditional, conservative sections of the printed media, our analysis reveals a surprising degree of willingness to adapt and learn new ways. In tracing the dynamics of this process we assess the extent to which a more enlightened appreciation of Mexican women's football only lasted for as long as they continued to win matches.